Credit Market Frictions and the Reallocation Process - Gadi Barlevy (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
In a seminal paper, Davis and Haltiwanger (1990) demonstrate that recessions are associated with an increase in job reallocation, at least in the manufacturing sector. The conventional view has interpreted this as evidence of "cleansing" effects: less productive jobs are destroyed in recessions, and resources are reallocated towards more productive uses. Thus recessions serve to improve allocative efficiency. This paper shows that when credit market frictions are introduced, the result can be reversed. That is, the most efficient jobs are destroyed in recessions, resourses are reallocated towards less productive uses, and misallocation is exacerbated.
Keywords: E24; E32; E44; 330; Credit Market Imperfections; Job Reallocation; the Cleansing effect